2021
DOI: 10.1063/5.0037298
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering at the nanoscale: A way forward to improve coronary stent efficacy

Abstract: Coronary in-stent restenosis and late stent thrombosis are the two major inadequacies of vascular stents that limit its long-term efficacy. Although restenosis has been successfully inhibited through the use of the current clinical drug-eluting stent which releases antiproliferative drugs, problems of late-stent thrombosis remain a concern due to polymer hypersensitivity and delayed re-endothelialization. Thus, the field of coronary stenting demands devices having enhanced compatibility and effectiveness to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 271 publications
0
24
0
1
Order By: Relevance
“…The study showed that in patients with acute coronary syndromes, CoCr-titanium-coated stents were non-inferior to the platinum-chromium biodegradable polymer, EES, in inducing major cardiac events at 12 months ( Tonino et al, 2020 ). Despite the biocompatibility of the target moiety and improved tissue specificity and cellular uptake ( Yin et al, 2014 ), nanoparticles, as a new generation of smart drug delivery materials, still require extensive research to evaluate their safety issues ( Cherian et al, 2021 ). In addition, clinical evaluation of polymer-free DES is also underway.…”
Section: Future Directionsmentioning
confidence: 99%
“…The study showed that in patients with acute coronary syndromes, CoCr-titanium-coated stents were non-inferior to the platinum-chromium biodegradable polymer, EES, in inducing major cardiac events at 12 months ( Tonino et al, 2020 ). Despite the biocompatibility of the target moiety and improved tissue specificity and cellular uptake ( Yin et al, 2014 ), nanoparticles, as a new generation of smart drug delivery materials, still require extensive research to evaluate their safety issues ( Cherian et al, 2021 ). In addition, clinical evaluation of polymer-free DES is also underway.…”
Section: Future Directionsmentioning
confidence: 99%
“…Specialized micro- and nano-patterns have been introduced on the stent surface to reduce the risk of blood clotting, expedite healing and improve endothelialization. The design of textures on the thin struts of a stent includes nanotubes, ridges, pores, diamonds, leafy structure, or even a pattern mimicking the shape of smooth muscle cells ( Cherian et al, 2021 ) ( Junkar et al, 2020 ). Importantly, the textures are assessed by preferential growth of endothelial cells over smooth muscle cells ( Cherian et al, 2020 ).…”
Section: Novel Developments and Challenges In Stentsmentioning
confidence: 99%
“…The exact parameters of the desired film can be customized by fine-tuning the electrostatic charge, the ion charge, the substrate, and the overall temperature. 168,169 The direct evaporation of an oligomer (Figure 6c) demonstrates the codeposition of monomers using a methodology where a polyelectrolyte aqueous solution containing one or two monomers was heated to evaporation and then selfassembled on the substrate.…”
Section: Surface-deposition Techniquesmentioning
confidence: 99%
“…The source material is heated under vacuum (generally up to 10 7 Torr) to achieve lower-temperature vaporization, completing the coating through deposition/sublimation on the substrate surface. The exact parameters of the desired film can be customized by fine-tuning the electrostatic charge, the ion charge, the substrate, and the overall temperature. , …”
Section: Surface-deposition Techniquesmentioning
confidence: 99%